Design of a safety training package for migrant workers in the construction industry. (April 2021) - Vignoli, Michela; Nielsen, Karina; Guglielmi, Dina; Mariani, Marco Giovanni; Patras, Luminita; Peirò, Jose Maria
Highlights: Gaps and challenges related to training for migrant workers in the construction sector are discussed. A new Safety Training Package (CSTP) for migrant workers in the construction sector is presented. The CSTP developed is according to second and third generation training principles. Abstract: The construction sector is known as a high-risk sector with many safety challenges. It is also characterised by a large number of migrant workers and these workers report higher accident rates than native workers. This paper presents the design of the CSTP (Construction Safety Training Programme). The CSTP is a theory-based training program aimed at improving safety behaviours in construction sites acknowledging the particular challenges migrant workers face. Based on second and third generational models of training, we developed a training program that addresses the challenges faced by migrant workers in the construction industry, namely language and cultural barriers, times pressures, difficult living conditions and separation between native and migrant workers, all of which may have a detrimental impact on a shared safety culture and joint understanding of the importance of safety performance. The CSTP consists of five modules, both face-to-face and online teaching to facilitate sensemaking and social learning. A crucial underlying element of the CSTP is the importance of not only technical skills, but also non-technical skills such as communication, teamwork, decision making, situational awareness and management of stress and fatigue. We propose that the strong theoretical learning principles embedded in the training program are likely to increase transfer of training that could help the construction sector develop safe working cultures.